MDA-7/IL-24 inhibits cell survival by inducing apoptosis in nasopharyngeal carcinoma - Lin, Cheng (Int J Clin Exp Med, 2014)
Aims: Nasopharyngeal carcinoma (NPC) is the most common primary malignancy of the nasopharynx. Due to its local recurrence and distant metastasis, conventional therapy is usually ineffective. MDA-7/IL-24 (melanoma differentiation associated gene 7), a member of the IL10 family of cytokines, inhibits growth of various human cancer cells, but the underlying mechanism is largely unknown. There is no report of mda-7 in nasopharyngeal carcinoma. We aimed to investigate the role of MDA-7/IL-24 in NPC. Methods: Immune defective adenoviral vector carrying the gene was produced, infected NPC CNE cells and observed its growth, cell proliferation, apoptosis and the effect of combination with chemotherapy. Results: The results showed that (1) MDA-7/IL-24 inhibited NPC CNE cell growth and survival; (2) mda-7 induced cell apoptosis and death; (3) MDA-7/IL-24 in collaboration with chemotherapy induced cell apoptosis significantly; (4) MDA-7/IL-24 induced cell apoptosis by down-regulation of anti-apoptosis molecules such as Bcl-2 and Bcl-xl and up-regulation of caspase 3. Conclusion: The results suggested that MDA-7/IL-24 had obvious therapeutic effect in NPC cells. It is verified that adenovirus mediated MDA-7/IL-24 represents a potentially important new approach to NPC therapy.